O incidente de desconsideração de personalidade jurídica e sua aplicação no redirecionamento da execução fiscal - Lima, Luciane Pimentel de (2018)
This paper’s purpose is to analyze the disregard of legal personality institute, provided for in article 50 of the Civil Code (CC) and that of tax liability, especially that provided for in 135, III, of the National Tax Code (CTN). It will be also studied the possibility of applying the Incident of Disregard of Legal Personality (IDPJ), innovation of the new Civil Procedure Code (Law nº 13.105/2015), regarding the tax foreclosure procedures